SFLP: arming fishermen with GPS to combat poachers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Peter Lowrey describes how small-scale fishermen in Guinea have traded in their submachine guns for GPS devices to combat foreign trawlers poaching in their fishing grounds.